(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
Torture is finally a crime, according to the new article nr. 613-bis of the Italian Criminal Code entered into force only in 2017. The prohibition of torture and cruel and inhuman treatment or punishment, as a matter of power, committed by agents of the State, is established in all international human rights conventions. In this light, the author questioned the compatibility of the Italian disposition to the concept of torture set at the international level. Special attention is paid to the detainees’ conditions and the respect for their rights. In prisons, individuals are particularly exposed to the risk of being victims of torture or ill-treatment because of the imbalance of power induced by deprivation of liberty.